Proposals by Sisters in Islam (SIS) pertaining to Ṭalāq issues: an analysis from an Islamic perspective = Cadangan oleh Sisters in Islam (SIS) mengenai isu-isu Ṭalāq; satu analisis dari perspektif Islam - Kamaruddin, Zuraidah; Yunus, Saidatolakma; Abdul Rahim, Adibah (IIUM Press, International Islamic University Malaysia, 2017)
Sisters in Islam (SIS) is a Non-Governmental Organization in Malaysia. The group suggested that some existing laws in the Shariah court be reformed to ensure that the Muslim women’s rights are protected under the law. Thus, the objective of this study is to analyze the proposed solutions by SIS on the selected issues related to the provisions of ṭalaq in the Islamic Family law that are implemented in the Shariah court in Malaysia. Then, the paper gives clarification in relation to it from an Islamic perspective. In the selected issues pertaining to ṭalÉq, the research found that SIS often comes up with their solutions without referring to any Qur’anic verses or the Hadith of the Prophet. Therefore, the researchers are in opinion that an analysis of SIS’s views on these selected issues should be done from an Islamic perspective. It is hoped that this study will provide an objective understanding on the issues of ṭalÉq from a correct perspective. In providing solutions and suggestions, SIS must refer to MaqÉÎid al-SharÊÑah. All solutions and recommendations must be parallel with the Qur’an and Hadith.